Arus Rip di Perairan Pesisir Pangandaran, Jawa Barat (Rip Current in Pangandaran Coastal Water, West Java) - Edi Kusmanto; Wahyu Budi Setyawan (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2013)
Perairan pesisir Pangandaran adalah bagian dari perairan pesisir Teluk Parigi dan merupakan bagian yang paling tenang. Keadaan tersebut menyebabkan pantai Pangandaran berkembang menjadi tempat tujuan wisata pantai yang terkenal. Penelitian dilakukan di bagian pantai dimana arus rip diketahui sering terjadi. Gambaran tentang arus rip dilakukan dengan pengamatan visual dan pendekatan analisis kondisi morfologi pantai, batimetri atau morfologi dasar laut, kondisi gelombang, kecepatan dan arah arus, serta kekeruhan. Hasil penelitian ini menunjukkan bahwa arus rip merupakan kejadian yang umum di kawasan pesisir Teluk Parigi, dan sering muncul di bagian tertentu pantai Pangandaran yang telah dipandang aman. Swell dengan kisaran periode 6,57– 8,91 dt dari Samudera Hindia dengan arah hampir tegak lurus garis pantai diduga merupakan gelombang pencetusnya. Hasil penelitian menunjukkan enam arus rip dengan kecepatan berkisar dari 0,8–1 m.dt-1. Rekaman data kekeruhan membuktikan arus rip tersebut membawa muatan sedimen dari tepi pantai ke tengah laut. Data batimetri di lokasi penelitian memperlihatkan adanya morfologi dasar laut yang bergelombang membentuk punggungan dan lembah memanjang dari pantai ke arah laut lepas. Posisi kejadian arus rip yang tidak spesifik di lembah atau punggungan menunjukkan tidak adanya kontrol morfologi dasar laut terhadap kejadian arus rip. Kata kunci: arus rip, swell, pantai pasir, perairan pesisir, Pangandaran Pangandaran coastal waters is coastal tourism site that situated at the calmest part of Parigi Bay coastal waters. The favorable coastal area condition has made the coastal zone growth to be favorite coastal tourism site. The study site was coastal segment where rip currents frequently occur. This research was conducted by visual observation of rip currents and coastal morphology analysis approach, bathymetry survey, wave conditions, the speed and direction of currents, and turbidity. Results of this study indicate that rip currents are common phenomena at the Parigi Bay coastal area, and the currents frequently occur at several parts of the Pangandaran coastal zone, which are supposed to be safe. The rip currents could be identified visually. Swell with periods of 6.57 to 8.91 s propagating from the Indian Ocean in nearly normal direction to the coastline of Pangandaran could be the cause of rip currents. During field work of this study, it was recorded the existing of six rip currents with speeds in the range of 0,8–1 m.s-1. Obtained backscatterance records indicated that the recorded rip currents transport sediment load seaward from swash zone. Bathymetry data records of the study area showed an existing of undulating submarine morphology with axis lines normal to coastline. However, position of the rip current occurrence had no a good correlation with the undulating morphology. The facts indicate that no control of seabed morphology on rip current occurrence.   Keywords: rip current, swell, sandy beach, coastal waters, Pangandaran